Spinning pulsating strings in $$(AdS_5 × S^5)_{\varkappa }$$ (AdS5×S5)ϰ - Sorna Prava Barik; Kamal L. Panigrahi; Manoranjan Samal (European Physical Journal C: Particles and Fields, 2018)
Abstract We study a general class of spinning pulsating strings in $$(AdS_5 × S^5)_{\varkappa }$$ (AdS5×S5)ϰ background. For these family of solitons, we examine the scaling relation between the energy, spin or angular momentum. We verify that in $$\varkappa → 0 $$ ϰ→0 limit these relations reduce to the undeformed $$AdS_5 × S^5$$ AdS5×S5 case. We further study an example of a string which is spinning in the $$\varkappa $$ ϰ -deformed $${\hbox {AdS}}_5$$ AdS5 and $${\hbox {S}}^5$$ S5 simultaneously and find out the scaling relation among various conserved charges.